UPAYA PENANGGULANGAN TINDAK PIDANA KORUPSI PADA MASA PANDEMI COVID-19 - Parapat, Yon Tado Wali Manda (Esensi Hukum, 2020)
Abstract The covid-19 Pandemic must be tackled quickly, both government and society. The covid-19 Pandemic changed the lives of all Indonesians. In disaster management, it is the responsibility of the government to provide management to provide protection for the community from the threat of natural disasters and to ensure the implementation of planned, integrated, coordinated and comprehensive disaster management. This study aims to determine the regulation of criminal acts of corruption that were carried out during the Covid-19 Pandemic, the penalties that will be given to perpetrators of corruption during the Covid-19 Pandemic and how to tackle corruption crimes during the Covid-19 Pandemic. The method used in this research is the Normative Juridical Method. Legal efforts in eradicating criminal acts of corruption carried out during the Covid-19 Pandemic carried out two strategies, namely preventive and repensive efforts. The community must fully support all Government policies. Keywords: Covid-19, Corruption, Prevention Abstrak Pandemi covid-19 harus ditanggulangi secara cepat, baik pemerintah ataupun masyarakat. Pandemi covid-19 mengubah kehidupan seluruh masyarakat Indonesia. Dalam penanganan bencana adalah tanggung jawab dari pemerintah memberikan penanganan terhadap memberi perlindungan masyarakat dari ancaman bencana alam dan menjamin terselenggarakannya penanggulangan bencana yang terencana, terpadu, terkoordinasi dan menyeluruh. Penelitian ini bertujuan untuk mengetahui pengaturan tindak pidana korupsi yang dilakukan pada saat Pandemi Covid-19, hukuman yang akan diberikan pada pelaku pidana korupsi pada masa Pandemi Covid-19 dan upaya penanggulangan tindak pidana korupsi pada masa Pandemi covid-19. Adapun metode yang digunakan dalam penelitian ini adalah Metode Yuridis Normatif. Upaya hukum dalam memberantas tindak pidana korupsi yang dilakukan pada masa Pandemi covid 19 melakukan dua strategi yaitu upaya preventif dan reprensif. Masyarakat harus mendukung penuh seluruh kebijakan Pemerintah. Kata Kunci: Covid-19, Korupsi, Penanggulangan